The role of interferons in ovarian cancer progression: Hinderer or promoter? - Liu, Taiqing; Li, Yinqi; Wang, Xiaoyu; Yang, Xiaodong; Fu, Yunhai; Zheng, Yeteng; Gong, Hanlin; He, Zhiyao (Frontiers in Immunology, 2022)
Ovarian cancer (OC) is a common gynecologic malignancy with poor prognosis and high mortality. Changes in the OC microenvironment are closely related to the genesis, invasion, metastasis, recurrence, and drug-resistance. The OC microenvironment is regulated by Interferons (IFNs) known as a type of important cytokines. IFNs have a bidirectional regulation for OC cells growth and survival. Meanwhile, IFNs positively regulate the recruitment, differentiation and activation of immune cells. This review summarizes the secretion and the role of IFNs. In particular, we mainly elucidate the actions played by IFNs in various types of therapy. IFNs assist radiotherapy, targeted therapy, immunotherapy and biotherapy for OC, except for some IFN pathways that may cause chemo-resistance. In addition, we present some advances in OC treatment with the help of IFN pathways. IFNs have the ability to powerfully modulate the tumor microenvironment and can potentially provide new combination strategies for OC treatment.